Edición latinoamericana como empresa improbable: César Aira en México (1994–2018). - Belén Riveiro, María (Latin American Research Review, 2023)
The history of world literature contains Latin American chapters such as the boom. In discussing the hypothesis that points to the democratization of literature, this article argues that universality and the possibility of transcending national frontiers are unequally distributed resources. This article analyzes the conditions that enable the Latin American circulation of the Argentine writer César Aira through the editions of his books in Mexico, central to the Spanish-language publishing sector. This analysis rethinks the polarization of the field of publishing, examines the ways presses react to the concentration and foreignization of the field, produces knowledge on an increasingly renowned writer, and argues the methodological productivity of the notion of publishing trajectories. The article suggests that presses are vital to study regional links and argues that midsized presses that build catalogs of Latin American literature are improbable enterprises.